Penerapan Konsep Pekarangan Pangan Bergizi dalam Menunjang Kebutuhan Gizi Masyarakat di Lembang Ke’pe’ Tinoring Kecamatan Mengkendek Kabupaten Tana Toraja Sulawesi Selatan - Maria Octaviane; Syamsul Rahman; Helda Ibrahim (SENTRI: Jurnal Riset Ilmiah, 2026)
Indonesia prioritizes the development of food security as a foundation for other sectors. Food security and the fulfillment of community nutrition are among the main indicators of human resource development. Indonesia still faces various nutritional problems, such as low consumption of vegetables and fruits, inadequate intake of micronutrients, and high prevalence of stunting and anemia in several regions. The success of utilizing home gardens cannot be separated from various factors, such as access to superior seeds and seedlings, cultivation knowledge, water availability, and the level of participation of family members (Sulistyawati et al., 2020). This study aims to describe the implementation of nutritious food home gardens by the community in Lembang Ke’pe’ Tinoring, to analyze the application of the nutritious food home garden concept in supporting the nutritional needs of the community in Lembang Ke’pe’ Tinoring, Mengkendek District, Tana Toraja Regency, and to identify factors influencing the success of implementing nutritious food home gardens, as well as to identify constraints and solutions in their implementation. The research approach uses a quantitative descriptive method, with a population of 70 members of farmer groups receiving the P2B program, and sampling conducted through purposive sampling. The variables studied include the implementation of the P2B concept and the fulfillment of community nutritional needs, with indicators consisting of yard area, group activeness, consumption of garden produce, and reduction in food expenditure. The results show that the utilization of nutritious food home gardens contributes fairly well to family nutrition and economic aspects, as indicated by an increase in family income through P2B categorized as good, fairly good family nutrition understanding, and adequate fulfillment of nutrition through P2B.